Analisis Komparatif Kinerja Keuangan Bank Umum Konvensional dan Bank Umum Syariah di Indonesia dengan Metode RGEC - Sonia Ulfa Fadila; Endang Hatma Juniwati; Fatmi Hadiani; Deiana Suherlan (Journal of Applied Islamic Economics and Finance, 2023)
This study aims to analyse and compare the financial performance of Conventional Commercial Banks as the Holding Company of Banks and Sharia Commercial Banks in Indonesia in 2016 – 2020 uses the RGEC method. The Risk Profile aspect uses the ratio of NPL, NPF, LDR, FDR. The Good Corporate Governance aspect uses the GCG composite rating. The Earnings aspect uses the ratio of ROA, ROE, BOPO. The Capital aspect uses the CAR ratio. This study uses a different test using the Independent Sample T-test and the Mann Whitney test. The output of this research is there is no difference in the NPL and NPF ratio. The ratio of LDR and FDR shows that there is a difference. There is no difference in performance on the GCG composite rating. In the aspect of earnings, ROA, ROE, and BOPO, it shows that there are differences in performance. The CAR ratio shows that there are differences in performance.